Adfluvial migration and passage of Steelhead before and after dam removal at a major Great Lakes tributary - Bunt, Christopher M.; Jacobson, Bailey (Frontiers in Ecology and Evolution, 2024)
Despite the importance of Great Lakes fisheries and the increasing popularity of dam removal as a method to restore river connectivity and increase fish passage, the adfluvial migration of Steelhead (Oncorhynchus mykiss) has been drastically understudied and only relatively few published studies have examined the impacts of dam removal on fish movement and timing. To help fill these knowledge gaps, spawning migrations of Great Lakes adfluvial Steelhead tagged in spring and fall were monitored for two years before and three years after removal of a dam that partially blocked upstream movement for 100 years. Removal of the dam not only reduced downstream delay and increased passage at the site of the dam removal itself, but increased travel speeds and increased passage at remaining upstream dams for both spring and fall run fish, underscoring the cumulative impact of successive dam passage on fish migration. Fall fish were most impacted by the dam removal and were able to pass not only the dam footprint, but, for the first time, were also able to pass both remaining upstream dams, allowing them to overwinter at locations closer to known spawning areas. For these fish, delay at the footprint was reduced from the order of 100+ days to < 1 hour and the number of days passage occurred compared to the number of days fish were present and blocked increased from 2% to 82%. The benefits of dam removal should ultimately equate to increases in fish production, as more critical habitat becomes reconnected and more fish are able to pass dams and arrive at spawning beds. The observation that fish are likely able to remain in better condition and retain more energy for continued migration and reproduction warrants further study.